The digital divide and population aging in Chile: diagnosis, public policies, and intergenerational impact - Petit Molano, David (Estado, Gobierno y Gestión Pública, 2025)
Chile is undergoing a rapid demographic transition, with projections indicating that by 2050, 24% of its population will be over the age of 60 in the context of low fertility (1.4 children per woman). Within that context, this article examines the digital divide from a multidimensional perspective, integrating demographic, economic, and technological data, focusing on intergenerational inequalities, particularly among older adults in the Valparaíso Region, presenting a preliminary diagnosis. Through a cross-referenced and comparative analysis of national surveys (CASEN, 2022; Criteria, 2024), national reports, and international standards (UNESCO, OECD), a systematic study of public policies and initiatives based on successful local, national, and international models (such as Estonia and Canada) is proposed. These initiatives aim to integrate infrastructure, digital literacy, and technological security to mitigate socioeconomic risks and promote intergenerational inclusion through long-term planning.